Structural colouration in Drosophila wings is thermally plastic and exhibits ecological variation - Garg, Divita; Dhotre, Kanak; Mayekar, Harshad Vijay; Singh Grewal, Raghwinder; Rajpurohit, Subhash (Frontiers in Ecology and Evolution, 2024)
IntroductionStructural colour patterns and their functions in insect wings are less known. Wing interference patterns (WIPs) are colour patterns apparent when wings are viewed against black backgrounds; the angle of incident light and wing surface structures also influence the resulting wing colour pattern. To date, WIPs are correlated with mate attraction, while the impact of geography and environment on WIPs remains unexplored. We explore WIP variation in Drosophila melanogaster populations collected from three altitudes and also compare WIP variation in sibling species D. melanogaster and D. simulans reared at three different temperatures to understand if local selection pressures could also influence WIPs.MethodologyWings of D. melanogaster males were collected from three different altitudes, and D. melanogaster and D. simulans males reared at three different temperatures were imaged. Images were analysed for their relative red, green and blue content in the RGB colour space. In representative images, wing thickness was assessed using the Newton colour series.ResultsAn altitudinal cline in WIPs was observed in the cosmopolitan D. melanogaster collected from the Western Himalayas. Relative RGB values and increase in altitudes were negatively correlated. Thermal responses in WIPs were parallel for both D. melanogaster and D. simulans. Relative RGB values were negatively correlated with rearing temperature. In both species, wing thickness measurements indicated that the wings of flies reared at low temperatures had greater blueness (cyan and magenta) compared to flies reared at moderate to high temperatures; the latter had more green and yellow content. Wing thickness pattern was also consistent for D. melanogaster flies collected from low versus higher altitudes.DiscussionWe find WIPs to be a plastic trait in response to temperature. WIP response to thermal variation corroborates with the temperature of the geographic origin in D. melanogaster. The adaptive significance of WIP variation and associated wing thickness remains unclear. Future studies could explore the underlying adaptive significance of structural colour patterning under different environmental conditions.